Habituasi Religius dalam Pendidikan Anak Usia Dini: Studi Kualitatif di Raudlatul Athfal Muslimat Al-Utsmani - Irfan Haris; Ulwi Albab (Hikamatzu | Journal of Multidisciplinary, 2025)
Religious character education in early childhood plays a strategic role in establishing children’s faith, moral values, and social behavior during the golden age of development. However, the implementation of religious character education in early childhood institutions often remains normative and lacks in-depth analysis of daily religious habituation practices. This study aims to analyze the process of instilling religious character values in early childhood through religious habituation activities in Class B of RA Muslimat Al-Utsmani. A qualitative descriptive approach was employed, utilizing participatory observation, in-depth interviews, and documentation. The research subjects included classroom teachers, the head of the institution, and students as supporting informants. Data were analyzed through data reduction, data display, and conclusion drawing, with source and technique triangulation to ensure data validity. The findings indicate that religious character values are systematically cultivated through prayer routines, religious content reviews, congregational dhuha prayer practices, teacher role modeling, and the integration of religious values into academic learning. These habituation practices positively contribute to children’s religious attitudes, discipline, orderliness, and learning readiness. This study highlights that structured and continuous religious habituation serves as an effective strategy for religious character education in Islamic early childhood education institutions